Keynote Article - Zervas, Efthimios (E3S web of conferences, 2024)
The 5th International Conference on Environmental Design and Health which took place on October 18-20, 2024, in Athens, Greece, in a hybrid format (in situ and online). This Conference aims to bring together researchers, academics and policy makers from around the world to discuss and share the latest innovations, research findings and practical applications in the field of Environmental Design, as well as health issues in relation to the environment. A total of 121 full presentations, 41 posters and two plenary lectures are held at the conference, which are divided into 13 thematic areas. The main points of those presentations are shown here.